2018
DOI: 10.1111/eff.12391
|View full text |Cite
|
Sign up to set email alerts
|

Generalist feeding strategies in Arctic freshwater fish: A mechanism for dealing with extreme environments

Abstract: Generalist feeding strategies are favoured in stressful or variable environments where flexibility in ecological traits is beneficial. Species that feed across multiple habitat types and trophic levels may impart stability on food webs through the use of readily available, alternative energy pools. In lakes, generalist fish species may take advantage of spatially and temporally variable prey by consuming both benthic and pelagic prey to meet their energy demands. Using stomach content and stable isotope analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…These results coincide with preliminary diet results suggesting that Yellow-billed Loons are generalist foragers that do not rely on one specific fish species and feed on whatever is present within the lake (Haynes et al, 2015). Similarly, fish species on the ACP are generalist foragers, which allows them to deal with the harsh environment in northern Alaska (Laske et al, 2018). We recognize that several factors could have reduced our ability to make inferences regarding the impact of fish populations on loon occupancy and productivity.…”
Section: Discussionsupporting
confidence: 82%
“…These results coincide with preliminary diet results suggesting that Yellow-billed Loons are generalist foragers that do not rely on one specific fish species and feed on whatever is present within the lake (Haynes et al, 2015). Similarly, fish species on the ACP are generalist foragers, which allows them to deal with the harsh environment in northern Alaska (Laske et al, 2018). We recognize that several factors could have reduced our ability to make inferences regarding the impact of fish populations on loon occupancy and productivity.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, the northern NR sturgeon populations experience a shortened feeding and growth season, potentially necessitating faster development or a more generalist strategy to feeding, as observed in Arctic freshwater fishes (Conover & Present, 1990;Laske et al, 2018), and thus resulting in higher condition than their southern counterparts throughout hatchery rearing. Irrespective of cause, these differences in mortality indicate population level differences in early development and should be further investigated.…”
Section: Effects Of Population and Early Acclimation On Mortality Growth And Conditionmentioning
confidence: 99%
“…Some abiotic stressors are environmentally correlated (e.g., hypoxia and toxic hydrogen sulphide are positively correlated in freshwater: Chen & Morris, 1972; Cline & Richards, 1969); individuals coping with toxicity from one physiochemical stressor must sometimes also survive in suboptimal conditions, leading to broad gene expression responses. In addition to selection from physiochemical stressors, we likewise see reduced species richness in many extreme environments (Greenway et al, 2014), which has been shown to impact behaviours (Plath et al, 2007; Tobler et al, 2009) and ecological interactions (Laske et al, 2018; Tobler & Plath, 2011; Tobler et al, 2015). We posit that similar mechanisms could be at play in Tar Creek, leading to broad stress‐related gene expression patterns.…”
Section: Discussionmentioning
confidence: 77%